Tillage effects on physical qualities of a vertisol in the central highlands of Ethiopia - Erkossa, Teklu (Academic Journals, 2011)
In the highlands of Ethiopia, tillage methods and frequency affect drainage, soil erosion, moisture conservation, weeding and harvesting of crops. This is through their effects on soil physical, chemical and biological qualities. In this study, four tillage methods for land preparation, "broad bed and furrows?,? green manure?, "reduced tillage "and the traditional tillage "ridge and furrows? were evaluated for their effects on soil physical quality indicators. The study was superimposed on the field experiment conducted on a vertisol area at Caffee doonsa for five years (1998 to 2002) in the central highland of Ethiopia. Penetration resistance (PR), aggregate stability, water-holding capacity, crust strength and thickness, texture, porosity, saturated hydraulic conductivity, bulk density and water holding capacity were the soil physical quality indicators considered. The result indicated that only PR was significantly (p<0.05) affected, where as the other parameter have shown a slight changes that are consistent with the effects on the bio-chemical parameters as previously reported. Broad bed furrows, and reduced tillage resulted in the highest and the lowest PR, respectively under both the moist and dry soil conditions. Green manure increased aggregate stability and reduced surface crust strength, which was linked to its increased organic matter content and consequent improved microbial activities.